Online Adaptation to Altered Auditory Feedback Is Predicted by Auditory Acuity and Not by Domain-General Executive Control Resources - Martin, Clara D.; Niziolek, Caroline A.; Duñabeitia, Jon A.; Perez, Alejandro; Hernandez, Doris; Carreiras, Manuel; Houde, John F. (Frontiers in Human Neuroscience, 2018)
When a speaker’s auditory feedback is altered, he adapts for the perturbation by altering his own production, which demonstrates the role of auditory feedback in speech motor control. In the present study, we explored the role of auditory acuity and executive control in this process. Based on the DIVA model and the major cognitive control models, we expected that higher auditory acuity and better executive control skills would predict larger adaptation to the alteration. Thirty-six Spanish native speakers performed an altered auditory feedback experiment, executive control (numerical Stroop, Simon and Flanker) tasks, and auditory acuity tasks (loudness, pitch and melody pattern discrimination). In the altered feedback experiment, participants had to produce the pseudoword “pep” (/pep/) while perceiving their auditory feedback in real time through earphones. The auditory feedback was first unaltered and then progressively altered in F1 and F2 dimensions until maximal alteration (F1 -150 Hz; F2 +300 Hz). The normalized distance of maximal adaptation ranged from 4 to 137Hz (median of 75±36). The different measures of auditory acuity were significant predictors of adaptation, while individual measures of cognitive function skills (obtained from the executive control tasks) were not. Better auditory discriminators adapted more to the alteration. We conclude that adaptation to altered auditory feedback is very well-predicted by general auditory acuity, as suggested by the DIVA model. In line with the framework of motor-control models, no specific claim on the implication of executive resources in speech motor control can be made.